Antibiotic Prescribing Practices for Upper Respiratory Tract Infections Among Primary Care Providers: A Descriptive Study. (17th June 2022) - Chandra Deb, Liton; McGrath, Brenda M; Schlosser, Levi; Hewitt, Austin; Schweitzer, Connor; Rotar, Jeff; Leedahl, Nathan D; Crosby, Ross; Carson, Paul
Abstract: Background: Most antibiotics are prescribed in the ambulatory setting with estimates that up to 50% of use is inappropriate. Understanding factors associated with antibiotic misuse is essential to advancing better stewardship in this setting. We sought to assess the frequency of unnecessary antibiotic use for upper respiratory infections (URIs) among primary care providers and identify patient and provider characteristics associated with misuse. Methods: Unnecessary antibiotic prescribing was assessed in a descriptive study by using adults ≥18 years seen for common URIs in a large, Upper Midwest, integrated health system, electronic medical records from June 2017 through May 2018. Individual provider rates of unnecessary prescribing were compared for primary care providers practicing in the departments of internal medicine, family medicine, or urgent care. Patient and provider characteristics associated with unnecessary prescribing were identified with a logistic regression model. Results: A total of 49 463 patient encounters were included. Overall, antibiotics were prescribed unnecessarily for 42.2% (95% confidence interval [CI], 41.7–42.6) of the encounters. Patients with acute bronchitis received unnecessary antibiotics most frequently (74.2%; 95% CI, 73.4–75.0). Males and older patients were more likely to have an unnecessary antibiotic prescription. Provider characteristics associated with higher rates of unnecessary prescribing included being in a rural practice, having more years in practice, and being in higher volume practices such as an urgent care setting. Fifteen percent of providers accounted for half of all unnecessary antibiotic prescriptions. Conclusions: Although higher-volume practices, a rural setting, or longer time in practice were predictors, unnecessary prescribing was common among all providers. Abstract : Patients with acute bronchitis received unnecessary antibiotics most frequently. Provider characteristics were associated with higher rates of unnecessary prescribing. Unnecessary prescribing was common among all providers. Fifteen percent of providers accounted for half of all unnecessary antibiotic prescriptions.